Correcting for the influence of ice‐rafted detritus on grain size‐based paleocurrent speed estimates. (30th October 2015) - Jonkers, Lukas; Barker, Stephen; Hall, Ian R.; Prins, Maarten A.
Abstract: The grain size of deep‐sea sediments provides an apparently simple proxy for current speed. However, grain size‐based proxies may be ambiguous when the size distribution reflects a combination of processes, with current sorting only one of them. In particular, such sediment mixing hinders reconstruction of deep circulation changes associated with ice‐rafting events in the glacial North Atlantic because variable ice‐rafted detritus (IRD) input may falsely suggest current speed changes. Inverse modeling has been suggested as a way to overcome this problem. However, this approach requires high‐precision size measurements that register small changes in the size distribution. Here we show that such data can be obtained using electrosensing and laser diffraction techniques, despite issues previously raised on the low precision of electrosensing methods and potential grain shape effects on laser diffraction. Down‐core size patterns obtained from a sediment core from the North Atlantic are similar for both techniques, reinforcing the conclusion that both techniques yield comparable results. However, IRD input leads to a coarsening that spuriously suggests faster current speed. We show that this IRD influence can be accounted for using inverse modeling as long as wide size spectra are taken into account. This yields current speed variations that are in agreement with other proxies. Our experiments thus show that for current speed reconstruction, the choice of instrument is subordinate to a proper recognition of the various processes that determine the size distribution and that by using inverse modeling meaningful current speed reconstructions can be obtained from mixed sediments. Key Points: IRD input spuriously suggests current speed changes Inverse modeling to unmix sediments yields meaningful current speed changes Analytical technique subordinate to recognition of sediment mixing